Work Readiness of Select Graduating Students of Mindanao State University Iligan Institute of Technology - D. MANALA-O, SAFA; J. MANULAT, SR., RHEDE NELSON (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
As thousands of students graduate each year, many find themselves unemployed because of skills gaps that are brought about by low work readiness levels. Work readiness is defined as the collection of soft and hard skills that emplayers require rom job applicants to be employed in a specific field. Literature claims that skills gap is a result of a variety of inherent factors in students, and a failure to establish links between schools and companies to prepare students with the right skills set currently demanded in the workplace. In response, this paper studied the work readiness levels of select graduating students from Mindanao State University Iligan nstitute of Technology (MSU-IIT) to investigate the presence of skills gaps with respect to the graduating students’ profile, and the relationship between such gaps, and the ethnicity and sex of the gradua ting students. Findings reveal that there are significant differences in the required and perceived workreadiness levels of all Business Management graduating students including Visayan, Moro, male and feale, but not for any of the of the computer Studies graduating students. the findings also establish a relationship between the differences noted for all graduating students sample and their ethnicity. Results show that Visayan graduating students tend to have smaller differences or skills gaps, thus have work readiness levels, than Moro graduating students.